Knygos muziejus ar muziejus apie knygą? - Ronkko, Marja-Liisa (Knygotyra, 2003)
In Finland, the debate about the need for a book museum was kindled in the mid-1990s. Vammala won the competition by abandoning the traditional museum idea and deciding to establish a more extensive institute and foundation to manage it, the Foundation for the Finnish Book Institute. The idea was to create a book information and know-how centre based on the concept „everything about books" yesterday, today and tomorrow. This ambitious idea seeks to generate new, innovative activities, to support book-related entrepreneurship and finally, in time, to establish a book museum in Finland. The aim of the Finnish Book Institute's programme is to consolidate the role of Vammala as a player in the book industry and to attract new residents, industry and craftsmen in the field, second-hand bookshops and other stores to the municipality, as well as to increase cultural and educational activities on a national and preferably even on a broader basis. This is why activities have been launched in digital form. EU funding has been obtained for 2001-2003 to develop the Institute's website.The official foundation of the Institute was established on Aleksis Kivi's Day, the Day of Finnish Literature, on 10 October 2002. The Finnish Ministry of Education had a vision of the Book Museum as a network of old collections of all libraries, museums presenting the history of the book, exhibitions and memorial rooms as well as other places that have attained museum status such as the homes of authors, private libraries, handicraft workshops and old printing presses. Also, the digital media concept aims at creating a databank on the book industry. Products of the research at the Finnish Book Institute would serve exhibition and publication activities, could include research and training material, seminars, electronic books, research presentations, registers of professionals in the business and discussion forums for the public at large. However, the real task is to highlight the cultural and historical significance of the book in an actual and symbolic context. A museum dedicated to the book is more than just a collection of books. It is a museum, the Museum of the Book, dedicated to the mind and language of man.